TRANSFORMASI MANAJEMEN SUMBER DAYA MANUSIA PENDIDIKAN TINGGI UNTUK MENINGKATKAN KOMPETENSI MAHASISWA DI ERA ARTIFICIAL INTELLIGENCE - Rohida, Leni; Sudiantini, Dian (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
Human resource management transformation in higher education environments is now a strategic need to face technological advances, especially in the field of Artificial Intelligence (AI). There are changes to improve student competency in order to compete in an increasingly complex and dynamic digital era. Based on previous literature reviews, most studies are still focused on the role of HR in the context of managing teaching and educational staff, as well as the application of digital technology in administrative aspects. This study offers scientific novelty with a framework of thought that HR transformation in higher education should be focused on improving student competency, not just internal HR management. The findings of the study indicate that updates in the training system, recruitment of teaching staff who have competency in technology, and the application of AI technology in the learning process have a significant contribution to improving student capabilities. Furthermore, adaptive and responsive HR management to technological developments has proven to be the key to success in this transformation. This study provides recommendations to universities so that they can strengthen HR capabilities through technology training programs and AI-based curriculum development. Thus, it is concluded that HR management transformation is an important factor that supports improving student competency in the era of artificial intelligence. This study can also be a valuable reference for higher education institutions in managing HR effectively and innovatively